Qualitative Exploration of Acculturation and Life‐Span Issues of Elderly Asian Americans. Issue 1 (8th April 2013) - Lee, Jee Hyang; Heo, Nanseol; Lu, Junfei; Portman, Tarrell Awe Agahe
<x xml:space="preserve">Abstract</x> Awareness of aging issues across diverse populations begins the journey toward counselors becoming culturally competent across client life spans. Understanding the life‐span experiences of cultural groups is important for helping professionals. The purpose of this research was to gain insight into the qualitative experiences of Asian American elders. The authors conducted semistructured interviews with 8 participants between September 2010 and March 2011 and analyzed the data using the Consensual Qualitative Research method. Findings indicate unique patterns in life‐span development with this population.